7(2n-5)=(9n+5)+1

Simple and best practice solution for 7(2n-5)=(9n+5)+1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(2n-5)=(9n+5)+1 equation:


Simplifying
7(2n + -5) = (9n + 5) + 1

Reorder the terms:
7(-5 + 2n) = (9n + 5) + 1
(-5 * 7 + 2n * 7) = (9n + 5) + 1
(-35 + 14n) = (9n + 5) + 1

Reorder the terms:
-35 + 14n = (5 + 9n) + 1

Remove parenthesis around (5 + 9n)
-35 + 14n = 5 + 9n + 1

Reorder the terms:
-35 + 14n = 5 + 1 + 9n

Combine like terms: 5 + 1 = 6
-35 + 14n = 6 + 9n

Solving
-35 + 14n = 6 + 9n

Solving for variable 'n'.

Move all terms containing n to the left, all other terms to the right.

Add '-9n' to each side of the equation.
-35 + 14n + -9n = 6 + 9n + -9n

Combine like terms: 14n + -9n = 5n
-35 + 5n = 6 + 9n + -9n

Combine like terms: 9n + -9n = 0
-35 + 5n = 6 + 0
-35 + 5n = 6

Add '35' to each side of the equation.
-35 + 35 + 5n = 6 + 35

Combine like terms: -35 + 35 = 0
0 + 5n = 6 + 35
5n = 6 + 35

Combine like terms: 6 + 35 = 41
5n = 41

Divide each side by '5'.
n = 8.2

Simplifying
n = 8.2

See similar equations:

| 11+5(2-x)=-3(x-3) | | V=3.14*2h | | -12=9x-6(2x+5) | | 9*(5*x-50)=0 | | A=4*3.14r | | 1/5*(-10)-2 | | 2x+1+6x=73 | | A=1/2(b+c) | | 35=-3x+13x-62 | | -4-2x=-26 | | 57=3x+6x+3 | | Y+6/5=Y+8/7 | | 1-0.4k=1 | | -6.4=-2.5tx | | 5a+2b=30 | | X-5*(-2)=-1 | | a-5=-24 | | -3+3=5s+21 | | -2a+21+6a=4a-7a | | 2*6=14-y | | ax+b=cx+2 | | 2x=14-(-2) | | 10x-19x=6x+1 | | 8+x/9=7 | | 4x-5x+20=-2 | | (x^2-3x+2)x=2184 | | -2x-2x=35-7 | | 12g+31h=-8g | | 0.4(7+2x)+1.1x=3.1 | | -9=4x-11 | | 4*-4+2*-2=-20 | | 12.25=0.25x+9 |

Equations solver categories